Comparative efficacy of intravenous premedication of clonidine versus nalbuphine on intraoperative hemodynamic profile of patients during surgery under general anesthesia: a randomized study - Agarwal, Salony; Samad, Abdul; Gupta, Kumkum; Singh, Raj Kumar; Srivastava, Ritesh; Baseer, Ans M. (International Journal of Research in Medical Sciences, 2019)
Background: Airway manipulation and surgical stimulation lead to variable changes in hemodynamic profile due to increase in plasma catecholamine levels, but these changes can be attenuated by appropriate premedication. The present study was designed to compare the clinical efficacy of intravenous premedication of clonidine with nalbuphine on intraoperative hemodynamic profile of patients during surgery under general anaesthesia. Methods: Sixty adult consenting patients of ASA physical status I and II of either gender were randomized into two groups of 30 patients each, to receive either intravenous clonidine (2 μg/kg) or nalbuphine (0.2 mg/kg), 10 min before induction with propofol. Direct laryngoscopy and intubation were facilitated with vecuronium bromide. Changes in heart rate, blood pressure and electrocardiogram were recorded at specific time intervals and were noted as primary variable. Any adverse effects and complications were recorded as secondary outcomes. Results: After laryngoscopy and intubation, the increase in mean heart rate and mean blood pressure occurred immediately in patients of both groups, but persisted up to 6 to 10 min in patients of clonidine group, thereafter the changes returned back to baseline values, while in patients of nalbuphine group, this increase persisted up to 8 to 10 min. The differences in hemodynamic changes between the groups were statistically significant throughout the surgery and post extubation. Conclusions: Intravenous clonidine was more effective than nalbuphine to attenuate the hemodynamics changes during stressful period of laryngoscopy, intubation and surgery.